Exploring the factors affecting the motivation for learning from the perspective of public health students: A qualitative study - Leila Allahqoli; Vinnaras Nithyanantham; Azam Rahmani; Azra Allahveisi; Reza Ghanei Gheshlagh; Arezoo Fallahi; Babak Nemat-Shahrbabaki (Journal of Mind and Medical Sciences)
Objective. Despite the significant role of motivation in achieving success among public health students, students often do not demonstrate adequate motivation for learning and education. This study was performed to determine factors affecting the motivation for learning from the perspective of public health students via content analysis approach. Methods. This qualitative study was conducted at Kurdistan University of Medical Sciences in Sanandaj, Iran in 2017. 15 students were included in the study by using purposive sampling. Data were collected through personal interviews, group discussions, and field notes, and they were analyzed through conventional content analysis. Several parameters were taken into account to support the accuracy and the strength of the data: acceptability, confirmability, and transferability. Results. Five categories were derived from the data analysis, including “University Policy”, “Health Status”, “Teacher’s Role”, “Student-Related Factors” and “University Facilities”. Attention to the health status and its priority in the opinion of people, authorities, and educational system were the most important factors involved in the students’ motivation for learning. Conclusions. To increase motivation for learning, students have diverse needs that should be met. Attention to the components of motivation for learning not only enhances academic achievement but also promotes the formation of health behaviors in the society.